Correlation of heavy metals in milk and drinking water - Davidov Ivana; Božić Aleksandar; Radinović Miodrag; Vranešević Milica; Davidov Nikola; Jurakić Željka (Biotechnology in Animal Husbandry)
This study investigates the potential correlation between heavy metal concentrations in drinking water and in the milk of dairy cows across three major regions of Vojvodina, Serbia: Srem, Banat, and Bačka. A total of 360 cows from 18 randomly selected dairy farms (six per region) were included in the study. From each farm, milk samples and drinking water samples were collected and analyzed for the presence of lead (Pb), cadmium (Cd), nickel (Ni), chromium (Cr), and arsenic (As). The aim was to determine the extent of transfer of these heavy metals from water into milk, which could pose a risk to both animal health and food safety. Correlation analyses were conducted separately for each region. Significant positive and negative correlations were observed between water and milk concentrations of specific metals, with notable regional differences. In Banat, strong positive correlations were found between Pb in water and Pb in milk (r = 0.953), and Ni in water and Ni in milk (r = 0.968). In contrast, Bačka and Srem showed more varied patterns, with both positive and negative correlations across the measured parameters. The findings highlight the need for continuous monitoring of water quality on dairy farms and their implications for milk safety in the region.